Dentinogenic differentiation potential of fast set white portland cements of a different origin on dental pulp stem cells - Ahmed, Hany Mohammed Aly; Luddin, Norhayati; Kannan, Thirumulu Ponnuraj; Mokhtar@Makhtar, Khairani Idah; Ahmad, Azlina (Wolters Kluwer - Medknow, 2017)
Background: Advances in endodontic biomaterials are at the forefront of endodontic research. Purpose: This study aimed to compare the dentinogenic differentiation potential of extracts of two formulations (normal and fast set [FS] by the addition of calcium chloride dihydrate (CaCl2.2H2O) of white Portland cements (WPCs) of a different origin (Aalborg, Malaysia, and Egypt) on dental pulp stem cells (DPSCs). Materials and Methods: The material extracts at 12.5 mg/ml were applied on DPSCs cultured in 96‑well plates. After 1, 3, 7 and 14 days of incubation, the RNA was extracted, cDNA was prepared, and the expression of four dentinogenic gene markers (bone gamma‑carboxyglutamate protein, dentin sialophosphoprotein, runt‑related transcription factor 2, and secreted phosphoprotein 1 [SPP1]) was examined using the real‑time polymerase chain reaction. One‑way analysis of variance was used for statistical analysis, and the level of significance was set at 0.05 (P = 0.05). Results: Significant differences were observed between Malaysian WPC (MAWPC) and Egyptian WPC (EGWPC) and FS MAWPC), FS EGWPC in 7 out of 15 and 6 out of 10 comparisons, respectively. While more expressions in EGWPC group were observed in four comparisons and three for MAWPC, all FS formulations showed higher expressions for FS MAWPC compared to FS EGWPC (P < 0.05). The addition of CaCl2.2H2O to MAWPC and EGWPC increased the upregulation of SPP1 gene at all‑day intervals, which was not observed with other genes. Conclusions: The dentinogenic differentiation of DPSCs shows different expression profiles to extracts of normal and fast formulations of WPC. Extracts of WPC of different origin have different dentinogenic differentiation potential on DPSCs. Keywords: Calcium chloride dihydrate, dentinogenic differentiation, Egypt, Malaysia, real‑time polymerase chain reaction, white Portland cement